Czech Republic: Social Law One Step Forward Two Steps Back - Štefko, Martin (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
This article analyses Czech Social Security law from the perspective of sustainability. The first part describes what is it, its position in the Czech legal order, and the level of protection given to welfare rights in the formal constitution. A social security system that is overly costly is not sustainable in the long term (the principle of financial sustainability). There are no real welfare rights in the constitution; they are rather constitutional ideas for legislature that must consider the health of the Czech economy. KEYWORDS: social security law, social benefits, occupational injuries